2018
DOI: 10.1109/jtehm.2018.2869091
|View full text |Cite
|
Sign up to set email alerts
|

Radial Pulse Spectrum Analysis as Risk Markers to Improve the Risk Stratification of Silent Myocardial Ischemia in Type 2 Diabetic Patients

Abstract: Diabetic patients with silent myocardial ischemia (SMI) have elevated rates of morbidity and mortality and need intensive care and monitoring. An early predictor of SMI may lead to early diagnosis and medical treatment to prevent progression and adverse clinical events. Therefore, this paper was aimed to evaluate the radial pulse spectrum as risk markers to improve the risk stratification of SMI in type-2 diabetic patients; 195 diabetic patients at high-risk of SMI were enrolled. All patients underwent myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Thus, we tried to use this technique and assess whether larger C4CV contributes to vascular risk in patients with type 2 diabetes (T2DM). Our cohort study on T2DM manifested that larger C4CV is associated with renal dysfunction (Liao et al 2018). Another study found that larger C4CV is associated with myocardial ischemia and a reduced left ventricular ejection fraction (<50%) (Liao et al 2018).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Thus, we tried to use this technique and assess whether larger C4CV contributes to vascular risk in patients with type 2 diabetes (T2DM). Our cohort study on T2DM manifested that larger C4CV is associated with renal dysfunction (Liao et al 2018). Another study found that larger C4CV is associated with myocardial ischemia and a reduced left ventricular ejection fraction (<50%) (Liao et al 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Our cohort study on T2DM manifested that larger C4CV is associated with renal dysfunction (Liao et al 2018). Another study found that larger C4CV is associated with myocardial ischemia and a reduced left ventricular ejection fraction (<50%) (Liao et al 2018). Recently, our preliminary study suggested that larger C4CV is independently associated with future major adverse cardiovascular events (MACE) in asymptomatic patients with T2DM (Liao et al 2019).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The harmonic analysis of arterial pulses has been used by researchers to study the frequency characteristics of organs; to explore the meridian theory in traditional Chinese medicine; to find the effect of herbs, coffee, acupunctures, fasting and exercise . It has also been used to link the harmonic spectrum with some cardiovascular risk factors in clinical monitoring …”
Section: Application Of the Pulse Diagnosismentioning
confidence: 99%